Fetomaternal outcome among elderly gravida and normal age group mothers - Deeksha, Deepa M.; Alagesan, Sujatha M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Advanced maternal age is defined as 35 years or more at estimated date of delivery is considered to have higher incidence of obstetric complications and adverse pregnancy outcome than younger women. Maternal age plays a vital role in pregnancy outcome. This study is instituted with the idea of identifying the association of advanced maternal age and adverse pregnancy outcome. Objective was to compare demographic characteristics and maternal outcome in elderly pregnancy in comparison with normal age group pregnancy. To compare perinatal outcome of elderly pregnancy with normal age group pregnancy. Methods: This was comparative case control study conducted at department of obstetrics and gynecology, Tirunelveli medical college hospital in 100 patients, about 50 in each of the 2 groups with maternal age > 35years and < 35 years. A group 1 (study group) was pregnant women of age >35 years and group 2 was pregnant women of age >18 years and<35 years. Pregnant women of age< 18 years and pregnant women having major medical disorders before pregnancy were excluded from study. Results: Among the study group incidence of artificial conception; spontaneous abortion; overt diabetes; chronic hypertension; preeclampsia; gestational hypertension ; fetal complications like FGR; shoulder dystocia were statistically significant. Conclusions: This study concludes that there is raised maternal morbidity and operative interventions needed with increasing age. Close monitoring for any complications is vital as early diagnosis and intervention will bring an excellent maternal and fetal outcome.